Direct Metal‐ and Reagent‐Free Sulfonylation of Phenols with Sodium Sulfinates by Electrosynthesis. Issue 28 (8th April 2019) - Nikl, Joachim; Lips, Sebastian; Schollmeyer, Dieter; Franke, Robert; Waldvogel, Siegfried R.
Abstract: A novel electrochemical strategy for the synthesis of aryl sulfones by direct sulfonylation of phenols with sodium sulfinates has been developed. The C, S‐coupling products are of particular interest for chemical synthesis, material sciences and pharmaceutical sciences. By using this metal‐ and reagent‐free electrochemical method, aryl and diaryl sulfones can be obtained directly in good yields. The established one‐step protocol is easy to perform, scalable, inherently safe, and enables a broad scope, which is not limited by quinoid‐forming substrates. Abstract : Two for one ! This electrochemical protocol for the sulfonylation of phenols uses sodium sulfinates as both the supporting electrolyte and coupling substrate. An 1, 1, 1, 3, 3, 3‐hexafluoroisopropanol (HFIP)‐directed anodic C, S‐cross‐coupling leads to the formation of aryl sulfones with yields up to 55 %. The scalable and inherently safe synthesis is managed in a sustainable, metal‐ and reagent‐free way (see scheme).